(3QSGdI aj GdYed HGdCSWQdGHs - (3CejI Hf YHO GdYRjR GdCfOdSj, CHh GdUdJ,J (B529 (3g` s
(3ChdgG (B:s
(3GdMeO ddg JYGdi NjQ eG GSJaJM Hg gPG cJGH jJVef ef GHhGH GdYed HGdGSWQdGH s
(3BNQgG (B:s
(3Odjd Gdadc GdeSJbje hEf cGf GcKQ aGfbUg aeG MUd ef GLRGA Odjd Gdadc GdeSJbje HYO GdRjGOI hGdfbUGf agh YOO GLQGA GdJSjQ Ke GdcJGH HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B845s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI eTgO (B- (3cdjI GdGdgjGJ s
Keywords: (3Gdadcs